Media Management of the ANTARA Central Kalimantan Online News Portal - Ananda, Annisa Rizki (Sinergi International Journal of Communication Sciences, 2024)
With online media presence, modern journalism has transformed into digital news platforms accessible through various features, including social media. One of the media outlets representing modern journalism is the online media platform of ANTARA National News Agency Central Kalimantan Bureau. As a branch of the national news agency, it plays a significant role in disseminating news and engaging audiences through digital strategies. This study aims to analyze the role of social media in online media management and how it influences audience engagement and content dissemination. The research employs a descriptive qualitative approach, utilizing interviews, documentation, observation, and document analysis as data collection methods. The findings indicate that the ANTARA National News Agency Central Kalimantan Bureau enhances the quality of news presentation, increases daily news publication, accelerates the news creation and broadcasting, and strengthens its social media presence. Furthermore, applying media management principles, particularly the 3E + 1N model and the inverted pyramid writing technique, contributes to its journalistic success. The study provides theoretical implications by demonstrating the evolving role of media management strategies in digital journalism, particularly in adapting to audience preferences and technological advancements.